Aplikasi Pemesanan Makanan Dan Minuman Pada Safaa Coffee Space Berbasis Mobile Android - Elvito Ruby Chenarna; Agusdi Syafrizal; Muchamad Zainul Rohman (CV MEDAN TEKNO SOLUSI, 2024)
Safaa Coffee Space, a coffee shop in Samarinda, faces issues with efficiency and comfort in its food and beverage ordering services due to cashier queues, leading to wasted time for customers and hindering the ordering process. This study aims to develop a mobile Android-based ordering application to enhance the efficiency and comfort of visitors. The identified problems include inefficient ordering processes and queue times that can diminish the customer experience. This research provides a solution by designing an ordering application that allows customers to select menus freely and place orders without having to queue at the cashier. The research methodology employs a prototype approach using the Dart programming language, the Flutter framework, and Firebase as the database. The results indicate that the application can improve the efficiency and comfort of visitors when ordering food and beverages. Black box testing demonstrates that all application features function properly. Additionally, the results of a questionnaire analysis involving 20 respondents show a satisfaction level of 78.4% with the application. Respondents were generally satisfied with the ease of use and the application's user interface, although there were suggestions for improving accessibility and the payment system.